2018
DOI: 10.1007/s00384-017-2958-6
|View full text |Cite
|
Sign up to set email alerts
|

Effect of immunonutrition on colorectal cancer patients undergoing surgery: a meta-analysis

Abstract: PurposeImmunonutrition has been used to prevent the complications after colorectal elective surgery. This systematic review aimed to analyze and assess the effect of immunonutrition on colorectal cancer patients who received elective surgery.MethodsThree electronic databases (Medline, Embase, Cochrane) were used to search the latent studies which investigated the effects of enteral immunonutrition (EIN) compared with standard enteral nutrition (EN) or parenteral immunonutrition (PIN) compared with standard par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(40 citation statements)
references
References 53 publications
1
36
0
Order By: Relevance
“…This acute nutritional deficiency is potentially modifiable and has been the target of nutritional optimization around the surgery time. Nutritional supplements enriched with immunonutrients have recently been introduced into clinical practice for patients undergoing cancer surgery (109). Theoretically, the role of these immunonutrients administered in the perioperative period could be similar in oncologic patients in order to decrease the incidence of surgical complications, in particular infectious complications.…”
Section: Immunonutrition As a Novel Ibd Therapeutic Approach?mentioning
confidence: 99%
“…This acute nutritional deficiency is potentially modifiable and has been the target of nutritional optimization around the surgery time. Nutritional supplements enriched with immunonutrients have recently been introduced into clinical practice for patients undergoing cancer surgery (109). Theoretically, the role of these immunonutrients administered in the perioperative period could be similar in oncologic patients in order to decrease the incidence of surgical complications, in particular infectious complications.…”
Section: Immunonutrition As a Novel Ibd Therapeutic Approach?mentioning
confidence: 99%
“…A meta-analysis of immunonutrition has been previously performed in colorectal cancer patients to study its functional mechanism and clinical use. Xu et al performed a direct comparison of meta-analyses comparing immunonutrition with standard nutrition in colorectal cancer patients who underwent surgery and suggested that regardless of the enteral or parenteral route and different nutrition formulas, immunonutrition was effective in reducing infectious complications and length of hospital stays (31). However, when comparing each immunonutrition formula alone with standard nutrition, the results suggested that different formulas had different advantages in clinical outcomes (14)(15)(16).…”
Section: Discussionmentioning
confidence: 99%
“…Immunonutrition is associated with reduced rate of complications and reduced length of stay [106,107] . In fact, it has been demonstrated that the administration of nutritional supplements containing mainly glutamine, arginine, omega-3 fatty acid and ribonucleic acid is able to reduce the inflammation and improve the immune response.…”
Section: Postoperative Nutritionmentioning
confidence: 99%
“…The mechanism of action of immunonutrition has not been fully clarified yet. Apparently, its main effect is to reduce bacterial translocation by maintaining the integrity of the intestinal mucosa and reducing its permeability, thus reducing the risk of infectious complications [107] .…”
Section: Postoperative Nutritionmentioning
confidence: 99%